Sizeable beta-strength in 31Ar (β3p) decay - Koldste, G.T. (2014)
We present for the first time precise spectroscopic information on the recently discovered decay mode β-delayed 3p-emission. The detection of the 3p events gives an increased sensitivity to the high energy part of the Gamow-Teller strength distribution from the decay of 31Ar revealing that as much as 30% of the strength resides in the β3p-decay mode. A simplified description of how the main decay modes evolve as the excitation energy increases in 31Cl is provided. © 2014 The Authors.